Beyond Administrative Formality: Marriage Registration as a Maqāṣid-Based Legal Protection in Indonesia - Wahyu Nur Cholis; Mowafg Abrahem Masuwd (Faculty of Shariah UIN Ponorogo, 2026)
This study analyzes the application of maqāṣid al-sharīah in marriage registration policies in Indonesia, aiming to bridge the tension between the validity of marriage under fiqh and the administrative obligations under positive law. The focus of the study is on the social and legal implications of the practice of nikah sirri on the protection of women’s and children’s rights within Muslim families. The study employs a legal-normative method with a conceptual and statutory approach. The analysis examines the doctrine of maqāṣid al-sharīah developed by al-Ghazali, al-Shatibi, and Jasser Auda, and relates it to marriage regulations in Indonesia. Data were analyzed qualitatively through a normative interpretation of the objectives of Islamic law and national law. The results indicate that marriage registration serves not only as an administrative procedure but also as a shar‘iyyah instrument that protects religion, life, intellect, lineage, and property. This study contributes to strengthening the normative legitimacy of the obligation to register marriages while supporting the enhancement of legal certainty, justice, and the public interest for Muslim families in Indonesia.